ERP-based introduction of MRP for process manufacturers using the example of Gerlinger Klebebandwerke GmbH & Co. KG - Gerlinger, Friedrich (2011)
This dissertation studies the suitability of discrete ERP systems for production planning, scheduling, and control in process manufacturing environments. In addition, a special focus is put on the specifics for small and medium enterprises (SMEs) in this context. The theoretical part focuses on literature research on the requirements for planning and scheduling to make MRP applicable in process industry production. The practical part is based on the implementation project of a company-wide ERP system upgrade at the German SME Gerlinger Klebebandwerke GmbH & Co. KG. The process manufacturer specialises in adhesive products for the construction, paper, and automotive industry. Findings from the literature are combined with the practical implications identified in interviews with company experts and in ERP training sessions. This combination of findings is used for a feasibility study that analyses the suitability of the ERP system chosen by Gerlinger for their manufacturing environment. In addition, conclusions regarding the generalist applicability of discrete ERP systems in process industry are drawn. The feasibility study reveals that the particular ERP system in question is suitable. In total, 90% of all necessary features are either fully supported in the standard version, or need workarounds to be applicable in Gerlinger’s production environment. Furthermore, the results suggest the general suitability of discrete ERP systems for batch and hybrid process manufacturers.